Hybrid channel gain prioritized access‐aware cell association with interference mitigation in LTE‐Advanced HetNets. (26th July 2016) - Gadam, M.A.; Ng, Chee Kyun; Nordin, Nor Kamariah; Sali, Aduwati; Hashim, Fazirulhisyam
Summary: LTE‐Advanced heterogeneous networks deployment is meant to address the increasing demand for quality of service, high data rates and coverage extension. Load balancing is among the primary challenges, especially when the user equipments (UEs) associate with diverse transmission power network tiers using received signal strength. The low‐power network tier's spectrum will be underutilized, and UEs associated with them will be inflicted by interference from the high‐power network tier. The proposed hybrid channel gain prioritized access (HCGPA)‐aware cell association scheme stresses the importance of combined metrics with interference mitigation to simultaneously achieve load balancing and enhance performance among the network tiers. The high‐priority UEs associate with the tier that gives the maximum channel gain being higher than a given threshold. While the low‐priority UEs association is based on the maximum joint metrics (channel gain, channel access probabilities of low‐priority UEs and high‐priority UEs). The HCGPA scheme has 1.72 times the number of UEs connected to low‐power networks, 8% better load balancing fairness, compared with the conventional reference signal receive power and RSRP + 6 dB bias cell associations. Although the susceptibility of HCGPA to interference led to the poor signal to interference to noise ratio (SINR) performance of the cell‐edge UEs, the cell‐centre UEs exhibited the best spectral efficiency performance. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper proposes a hybrid cell association scheme that stresses the importance of combined metrics in a two‐tier network. The high‐priority user equipments (UEs) associate with the tier that gives the maximum channel gain being higher than a given threshold, while the low‐priority UEs association is based on the maximum joint metrics (channel gain, channel access probabilities of low‐priority UEs and high‐priority UEs). Simulations and analysis show that the proposed hybrid channel gain prioritized access‐aware scheme can significantly improve the network performance and load balancing fairness.